2020
DOI: 10.1002/acm2.12997
|View full text |Cite
|
Sign up to set email alerts
|

Validation of PTV margin for Gamma Knife Icon frameless treatment using a PseudoPatient® Prime anthropomorphic phantom

Abstract: The Gamma Knife Icon allows the treatment of brain tumors mask‐based single‐fraction or fractionated treatment schemes. In clinic, uniform axial expansion of 1 mm around the gross tumor volume (GTV) and a 1.5 mm expansion in the superior and inferior directions are used to generate the planning target volume (PTV). The purpose of the study was to validate this margin scheme with two clinical scenarios: (a) the patient’s head remaining right below the high‐definition motion management (HDMM) threshold, and (b) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…This hollow phantom can be printed with bone-mimicking materials based on anatomical structures of a past patient, based on CT data or scans, and it is filled with water and a 3D polymer gel dosimeter insert to simulate soft tissue equivalence. 30 Irradiation of this gel phantom provides the ability to evaluate 3D dose distributions for SRS. 18,31,32 The custom phantom is designed with a glossy white exterior, which is incompatible with the SGRT cameras.…”
Section: Rtsafe Prime Phantommentioning
confidence: 99%
See 1 more Smart Citation
“…This hollow phantom can be printed with bone-mimicking materials based on anatomical structures of a past patient, based on CT data or scans, and it is filled with water and a 3D polymer gel dosimeter insert to simulate soft tissue equivalence. 30 Irradiation of this gel phantom provides the ability to evaluate 3D dose distributions for SRS. 18,31,32 The custom phantom is designed with a glossy white exterior, which is incompatible with the SGRT cameras.…”
Section: Rtsafe Prime Phantommentioning
confidence: 99%
“…30 Irradiation of this gel phantom provides the ability to evaluate 3D dose distributions for SRS. 18,31,32 The custom phantom is designed with a glossy white exterior, which is incompatible with the SGRT cameras. A nude makeup foundation (Stay Matte, Rimmel, London) was applied to the phantom's surface to simulate a skin tone visualizable by the scanner units.…”
Section: Rtsafe Prime Phantommentioning
confidence: 99%
“…Also, a more practical approach might be to choose a value close to the recommended amount from this work, say 1 mm, for instance, to implement as setup margin, but which is similar to that predicted by the VHMF or Parker formulae (Table 4). Utilizing a similar approach of 1 mm for PTV margin (1.5 mm superior and inferior), a recent phantom study demonstrated acceptable dose delivery even under the worst-case scenario for frameless radiosurgery with Gamma Knife Icon [27]. In any situation, rational margin application should seek to balance the risk of normal tissue injury from radiation treatment with the risk of injury to the same tissue due to uncontrolled disease [28].…”
Section: Discussionmentioning
confidence: 99%
“…The phantom is a 3D‐printed anatomical replica created from a CT image of a human head. The hollow phantom with internal anatomical bony structures can be filled with water and has an insert to hold an ionization chamber for point dose measurement 17 . Recently, RTsafe developed a new delineation insert that fits into their Prime phantom with two predefined brain metastatic lesions near brainstem that are visible on MRI (Figure 1a).…”
Section: Methodsmentioning
confidence: 99%
“…The hollow phantom with internal anatomical bony structures can be filled with water and has an insert to hold an ionization chamber for point dose measurement. 17 Recently, RTsafe developed a new delineation insert that fits into their Prime phantom with two predefined brain metastatic lesions near brainstem that are visible on MRI (Figure 1a). The superior target has a volume of 4.8 cm 3 , the inferior target has a volume of 1.4 cm 3 , and the density of both targets is 1.03 g/cm 3 .…”
Section: Head Phantom With Delineation Insertmentioning
confidence: 99%